The contribution of head movement to the externalization and internalization of sounds. - W Owen Brimijoin; Alan W Boyd; Michael A Akeroyd (PLoS ONE)
Background When stimuli are presented over headphones, they are typically perceived as internalized; i.e., they appear to emanate from inside the head. Sounds presented in the free-field tend to be externalized, i.e., perceived to be emanating from a source in the world. This phenomenon is frequently attributed to reverberation and to the spectral characteristics of the sounds: those sounds whose spectrum and reverberation matches that of free-field signals arriving at the ear canal tend to be more frequently externalized. Another factor, however, is that the virtual location of signals presented over headphones moves in perfect concert with any movements of the head, whereas the location of free-field signals moves in opposition to head movements. The effects of head movement have not been systematically disentangled from reverberation and/or spectral cues, so we measured the degree to which movements contribute to externalization. Methodology/principal findings We performed two experiments: 1) Using motion tracking and free-field loudspeaker presentation, we presented signals that moved in their spatial location to match listeners' head movements. 2) Using motion tracking and binaural room impulse responses, we presented filtered signals over headphones that appeared to remain static relative to the world. The results from experiment 1 showed that free-field signals from the front that move with the head are less likely to be externalized (23%) than those that remain fixed (63%). Experiment 2 showed that virtual signals whose position was fixed relative to the world are more likely to be externalized (65%) than those fixed relative to the head (20%), regardless of the fidelity of the individual impulse responses. Conclusions/significance Head movements play a significant role in the externalization of sound sources. These findings imply tight integration between binaural cues and self motion cues and underscore the importance of self motion for spatial auditory perception.